Meningkatkan Kemampuan Berfikir Kritis Melalui Pembelajaraan Berbasis Projek Menggunakan Media Origami (PTK Di TK At-Thoriq Kabupaten Kepahiang) - Sumarni, Titin; Asnawati, Asnawati; Fadilla, Rohayu (Early Childhood Research and Practice, 2025)
The purpose of this study was to improve critical thinking skills through project-based learning using origami media in children at Tk At-Thoriq Kepahiang Regency, to find out how children improve critical thinking in project learning using origami media, Classroom Action Research (PTK) which is focused on the classroom situation, which is used in the form of a cycle. The main subjects in this study were 10 children of Tk At-Thoriq Kepahiang Regency. Data collection techniques using observation and documentation methods. Data analysis was carried out descriptively qualitative-quantitative with the emphasis used to determine the improvement of the process expressed in a predicate, while quantitative data analysis was used to determine the improvement of results using percentages. The conclusion of the study that children's intelligence in critical thinking skills in learning using origami media in children of Tk At-Thoriq Kab Kepahiang Developed very well.